2021
DOI: 10.1002/ar.24736
|View full text |Cite
|
Sign up to set email alerts
|

A human craniofacial life‐course: Cross‐sectional morphological covariations during postnatal growth, adolescence, and aging

Abstract: Covariations between anatomical structures are fundamental to craniofacial ontogeny, maturation, and aging and yet are rarely studied in such a cognate fashion. Here, we offer a comprehensive investigation of the human craniofacial complex using freely available software and MRI datasets representing 575 individuals from 0 to 79 years old. We employ both standard craniometrics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 62 publications
2
8
0
Order By: Relevance
“…However, the relationships were negatively signedthat is shape changes were linked to decreases of relative brain sizes during ontogeny, rather than increases. Similar decreases in relative brain sizes have been observed during human postnatal life as well (Jeffery et al, 2022). Overall, the strongest relationship of cranium shape reported here involved the neuro-facial index, and the prominence of the face in our analyses is consistent with previous studies of other primates, including humans (e.g.…”
Section: Spatial-packingsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the relationships were negatively signedthat is shape changes were linked to decreases of relative brain sizes during ontogeny, rather than increases. Similar decreases in relative brain sizes have been observed during human postnatal life as well (Jeffery et al, 2022). Overall, the strongest relationship of cranium shape reported here involved the neuro-facial index, and the prominence of the face in our analyses is consistent with previous studies of other primates, including humans (e.g.…”
Section: Spatial-packingsupporting
confidence: 92%
“…Various kinematic, structural and physiological limitations on the overall size and growth of the head mean its constituent tissues are not all necessarily free to simultaneously adopt their genetically favoured size and shape (form) during ontogeny. Some must adapt their form, either transiently or permanently, via signalling mechanisms and plastic deformation as the spatial demands of other tissues prevail (see Jeffery et al, 2021Jeffery et al, , 2022. Whilst many researchers consider the brain the most important influence within this morphological milieu, it is widely recognised that other soft tissues can help sculpt the genetic expression of head form and that the brain itself is not an immutable agent.…”
Section: Introductionmentioning
confidence: 99%
“…4 A ) remain to be elucidated along similar lines of evidence. MRI-based studies have revealed structural changes in the brain after the completion of brain growth, especially in the frontal cortex during adolescence ( 13 , 19 , 25 ). However, these changes have only little effect on the shape of the endocast and cannot account for endocranial shape change from immature to adult fossil H. sapiens ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other external constraints also influence endocranial shape. Overall, evolutionary and developmental changes in endocranial shape are due not only to intrinsic changes in the brain but also to extrinsic factors such as the changing proportions of the neurocranium (the skull region enclosing the brain) relative to the viscerocranium (the face and cranial base) ( 7 , 13 ). Facial size in members of the H. sapiens species lineage gradually reduced during the past 200–300 ka ( 14 ), a period during which techno-cultural changes and changes in subsistence strategy had impacts on facial size and shape as well as on masticatory function ( 15 ).…”
mentioning
confidence: 99%
“…lower sexing accuracy for the 12–15 years' age interval probably as a result of differences in the development of boys and girls during puberty). Another study based on the analysis of magnetic resonance imaging datasets (Jeffery et al, 2022) revealed size‐dependent sexual differences in craniofacial variation well before puberty.…”
Section: Introductionmentioning
confidence: 99%